canN2Onet—a Canadian nitrous oxide collaboration network to meet greenhouse gas emission reduction targets - Erin J Daly; David Burton; MacDonald Graham K; Kari Dunfield; Tongzhe Li; Alfons Weersink; Mario Tenuta; Kate A Congreves; Bobbi Helgason; Tristan Skolrud; Thomas Andrew Black; Henrique Da Ros Carvalho; et al. (Environmental Research Letters, 2025)
The application of nitrogen (N) fertilizer to agricultural soils results in the emission of nitrous oxide (N _2 O), accounting for ∼40% of Canada’s and 10% of global agricultural greenhouse gas emissions. Reducing these emissions through N fertilizer best management practices (BMPs) is critical to achieve the fertilizer-related emission reduction target of 30% below 2020 levels by 2030 set by the Canadian government. However, progress is hindered by several key challenges: (1) the need to quantify N _2 O emission reductions associated with BMPs, (2) an incomplete understanding of the behavioral factors influencing the adoption of BMPs, (3) the lack of suitable metrics to track progress towards reduction targets, and (4) an absence of region-specific management recommendations that balance emission reduction potential with farm profitability and farmer decision-making. To address these challenges, we introduce can N _2 O net , an innovative collaborative network formed in 2024 and comprising a diverse range of experts from institutions across Canada with partners representing academia, industry, government, and producer organizations. can N _2 O net is focused on (1) the establishment of a national network of benchmark sites linking year-round N _2 O emission measurements and soil processes with behavioral economic studies on decision-making processes; (2) development and validation of robust metrics for tracking progress towards emission reduction targets by utilizing Canada’s first regional tower measurements, database development, and enhanced biogeochemical models; and (3) creation of a roadmap for emission reduction by up-scaling BMPs to the regional level, incorporating economic trade-offs and behavioral insights. This work represents the first coordinated national effort to generate a comprehensive understanding of N _2 O mitigation potential from improved management practices across Canada’s major grain and oilseed-producing regions. It offers actionable farm-level metrics reflective of real-world agricultural conditions and a transferable framework to guide region-specific nutrient management strategies globally, advancing both climate goals and agricultural sustainability.